Life cycle cost impact of maintenance networks for product-service system fleets - Schneider, Jannik; Mozgova, Iryna; Lachmayer, Roland

Procedure to Create an Automated Design Environment for Functional Assemblies - Altun, Osman; Kutay, Y; Mozgova, Iryna; Lachmayer, Roland

Ontology-Based Documentation of Quality Assurance Measures Using the Example of a Visual Inspection - Sheveleva, Tatyana; Herrmann, Kevin; Wawer, Max Leo; Kahra, Christoph; Nürnberger, Florian; Koepler, Oliver; Mozgova, Iryna; Lachmayer, Roland; Auer, Sören

Technical Inheritance as an Approach to Data-Driven Product Development - Lachmayer, Roland; Mozgova, Iryna (Design Methodology for Future Products)

Corporate Strategy Based Quantitative Assessment of Sustainability Indicators at the Example of a Laser Powder Bed Fusion Process - Wurst, Johanna; Schneider, Jannik; Ehlers, Tobias; Mozgova, Iryna; Lachmayer, Roland

Parametrization of a Hybrid Component Production Process Chain Based on Semantically Annotated Data. - Wawer, Max Leo; Sheveleva, Tatyana; Koepler, Oliver; Nürnberger, Florian; Mozgova, Iryna

Normalization Matrix for Sustainability Assessments Considering the Laser Powder Bed Fusion Process - Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland

Management of Research Field Data Within the Concept of Digital Twin - Dierend, Hauke; Altun, Osman; Mozgova, Iryna; Lachmayer, Roland

DigiBody - Digitale Prozesskette zur Abbildung und Optimierung der Fügetechnik im Rohbau - Jamei, Said; Döller, Norbert; Lossau, Sebastian; Beule, Felix; Al Trjman, Mohamad; Aubel, Tobias; Meschut, Gerson; Sommer, Daniel; Facciotto, Silvio; Droste, Alexander; Haufe, Andre; Helbig, Martin; et al. (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

A new viscoelastic-viscoplastic constitutive formulation in LS-DYNA to model adhesives during the complete manufacturing-crashworthiness process chain - Klöppel, Thomas; Haufe, Andre; Helbig, Martin; Liebold, Christian; Beule, Felix; Al Trjman, Mohamad; Aubel, Tobias; Meschut, Gerson; Jamei, Said; Fürle, Fabian; Lossau, Sebastian; Droste, Alexander; et al. (4a-Technologietage 2022)

Fortschrittskontrolle der Modellierung mechatronischer Produkte - Gräßler, Iris; Wiechel, Dominik; Thiele, Henrik (Tagungsband der Fachtagung VDI-Mechatronik)
Die Anforderungen an die Entwicklung mechatronischer Systeme sind seit der Erstfassung der VDI Richtlinie 2206 im Jahr 2004 stetig gestiegen. Nach einer umfassenden Überarbeitung ist 2021 die Richtline im Weißdruck neu veröffentlicht worden. Neben dem Systemdenken als gestärktes Kernelement des V-Modells und sechs Kontrollpunkten nur Gliederung der sachlogischen Aufgaben ist die durchgängig explizite „Modellierung und Analyse“ eine wesentliche Neuerung der Richtlinie. Da sich die Kontrollfragen nur auf den Entwicklungsprozess im Ganzen beziehen, wird durch die Betrachtung der Modellierung eines Batteriesystems aus einem Entwicklungsprojekt eines deutschen Automobilherstellers die folgende Forschungsfrage betrachtet: Welche spezifischen Kontrollfragen zu Fortschritt und Reifegrad der Modellierung eines Batteriesystems können aus den Kontrollpunkten des V-Modells (VDI 2206:2020) gefolgert werden? Als Ergebnis der Forschung liegen hinsichtlich der Modellierung eines spezifischen Systems detaillierte Kontrollfragen vor, die eine methodische Unterstützung für die modellbasierte Systementwicklung komplexer mechatronischer Systeme bieten. Zusätzlich ermöglichen sie der Projektleitung die Überprüfung des aktuellen Status der Entwicklung und sichern die Vollständigkeit des Systemmodells ab.

Approach to Sustainability-Based Assessment of Solution Alternatives in Early Stages of Product Engineering - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Sustainable product engineering is becoming increasingly important. This includes the development of environmentally friendly products and the design for recycling. In this paper a holistic method for the assessment of solution alternatives is presented, in which the stakeholder perspectives along the generic product lifecycle are taken into account. Finally, a new visualization is presented. By visualizing the results in the integrated sustainability triangle, decision-makers in product development can holistically assess the sustainability of the solution alternatives.
Keywords: sustainability; decision making; generic product lifecycle; design analysis; ecodesign

Model-Based Effect-Chain Analysis for Complex Systems - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Preuß, Daniel; Oleff, Christian (Proceedings of the Design Society)
Abstract Effect chain modeling approaches are applied to model cause-effect relations and analyze affected elements and dependencies. In this paper a systematic literature research is conducted to derive main characteristics and limitations of existing approaches. Then, the Model-based Effect Chain Analysis (MECA) method is introduced. Evaluation proves applicability of the method by means of a case example. This is done in the context of a project with a German automotive company. In the project 66 workshops were conducted to model certification-compliant effect chains in accordance to the UN ECE 156.

Untersuchung essenzieller Eigenschaften wasserlöslicher Polymere für die Anwendung zur Polymerpulverherstellung - Zhang, Xiandong; Neukötter, Moritz

Entwicklung einer Anlage zur Pulverabscheidung im Filament Extension Atomization Prozess - Schott, Alicia; Neukötter, Moritz

Heat Treatments of Metastable β Titanium Alloy Ti-24Nb-4Zr-8Sn Processed by Laser Powder Bed Fusion - Hein, Maxwell; Lopes Dias, Nelson Filipe; Pramanik, Sudipta; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (Materials)

Development of a test method for investigating the leak tightness of hybrid joined battery housing connections - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)
Keywords: Polymers and Plastics; General Chemical Engineering; Biomaterials

Fatigue strength of adhesively butt-bonded hollow cylinders under multiaxial loading with constant and variable amplitudes - Hecht, Matthias; Baumgartner, Jörg; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

Increasing the Prediction Quality of Clinching Process Simulation with Extensible Die by Means of Friction Modeling as a Function of the Local Joining Process Parameters - Rossel, Moritz Sebastian; Meschut, Gerson

Modeling and analysis of functional variance of complex technical systems - Menninger, Bastian; Wiechel, Dominik; Rackow, Sascha; Höpfner, Gregor; Oleff, Christian; Berroth, Joerg; Gräßler, Iris; Jacobs, Georg (DS 119: Proceedings of the 33rd Symposium Design for X (DFX2022))

Integrating Future Energy, Material and Production Scenarios in Life Cycle Engineering of Automotive Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Proceedings of the 17th Conference on Sustainable Development of Energy, Water and Environment Systems)

Individualisierung des ÖPNV - Integration technischer und sozialer Dimensionen nachhaltiger Mobilität - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas; Weyer, Johannes; Cepera, Kay; Adelt, Fiabian (14. Wissenschaftsforum Mobilität)

Menschenzentrierte Montageplanung und -steuerung durch fähigkeitsorientierte Aufgabenzuordnung - Gräßler, Iris; Roesmann, Daniel

Pulver im 3D-Druck - von Mascarabürsten bis zum Interieur eines Mini-Coopers (Vortrag) - Kletetzka, Ivo; Klippstein, Sven Helge (3D-DRUCK HAUTNAH - Der Einfluss einer Zukunftstechnologie auf unser Leben)

Untersuchung und Modellierung der Materialeigenschaften von glaskugelgefüllten, im Lasersinterprozess verarbeiteten Dry-Blends - Hanselle, Felix Paul

Oberflächenmodifikation von Glaskugeln zur Verbesserung der Adhäsion im Lasersinterverfahren - Kosanke, Maren

Potenzialanalyse für die Nutzung additiver Fertigungsverfahren bei einem Büromöbelhersteller und Realisierung eines Beispielbauteils (Studienarbeit) - Henke, Frederic

Einfluss des Lasersinter-Prozesses auf die Recyclingfähigkeit von flammgeschütztem PA12 Pulver - Ostermeier, Jakob

Einfluss der Lagerdauer von PA12- Lasersinterpulver auf die Verarbeitungs- und Bauteileigenschaft - Sural, Ilknur

Influence of laser-generated surface micro-structuring on the intrinsically bonded hybrid system CFRP-EN AW 6082-T6 on its corrosion properties - Delp, Alexander; Freund, Jonathan; Wu, Shuang; Scholz, Ronja; Löbbecke, Miriam; Haubrich, Jan; Tröster, Thomas; Walther, Frank (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Experimental Investigation of the Influence of different Bond Tool Grooves on the Bond Quality for Ultrasonic Thick Wire Bonding - Hagedorn, Oliver Ernst Caspar; Broll, Marian; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (CIPS 2022 - 12th International Conference on Integrated Power Electronics Systems)
To achieve optimum bond results at ultrasonic bonding thick copper wire on sensitive components is quite challenging. Bearing in mind that high normal force and ultrasonic power are needed for bond quality but as well increase stress and finally failure risk of the substrate, methods should be found to achieve high bond quality even at lower bond parameters. Therefore, bond experiments with different bond tool grove geometries have been conducted for copper and aluminum wire on direct copper bonded (DCB) substrates to investigate the impact of geometric parameters on bond formation and bond quality. The wire material depending impact of geometry changes on the bond formation and deformation was quantified. Additionally, a bonding parameter design of experiments (DOE) has been conducted for the reference and the most promising groove geometry. Higher shear values were achieved at reduced vertical tool displacement for most bonding parameter combinations, compared to the reference tool. This behavior allows for reducing ultrasonic power to obtain equal shear values; consequently, mechanical stresses in the interface decrease. This could potentially reduce the risk of chip damage and thus yield loss.

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Condition Monitor)

Experimental Investigation of Multidimensional Ultrasonic Heavy Wire Bonding - Scheidemann, Claus; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (2022 IEEE 9th Electronics System-Integration Technology Conference (ESTC))
ue to the constantly growing energy demand of power electronics and the need to reduce the size of electronic components like power modules for e-mobility, new challenges arise for ultrasonic wire bonding: the electrical connection must endure higher thermal and mechanical stress while the connecting partners become more sensitive or require more energy to get bonded. Past investigations have shown already that multi-dimensional ultrasonic bonding and welding yield the same or even better bond quality while reducing the load on the components. This contribution is intended to show whether multidi-mensional thick wire bonding is a promising concept to over-come the new challenges. The focus is on experimental investi-gations of different bond tool trajectories in ultrasonic wire bonding of aluminum and copper wire on DCB's and chips. The bond quality is analyzed by shear tests, microsections and, in the case of aluminum bonding, by a new machine learning method for an objective automated evaluation of the sheared area.

Regelungstechnik. Einführung in die Methoden und ihre Anwendung - Föllinger, Otto; Konigorski, Ulrich; Lohmann, Boris; Roppenecker, Günter; Trächtler, Ansgar

Patent DE 10 2017 000 926 B4: Gerät mit wenigstens einem elastisch verformbaren Bauteil, insbesondere einem Gummi-Metall-Lager und mit einer Einrichtung zur Feststellung des Beginns einer verschleißbedingten Bauteil-Restnutzungsdauer, sowie Verfahren zur Bestimmung der Bauteil-Restnutzungsdauer. - Reinke, Kai; Bender, Amelie; Meyer, Tobias; Sextro, Walter; Kimotho, James Kuria
Die Erfindung betrifft ein Gerät mit wenigstens einem elastisch verformbaren Bauteil als Strukturteil und/oder Lagerteil, auf das im Betriebsverlauf von wechselnden Betriebszuständen abhängige, unterschiedliche Verformungskräfte einwirken, die zu einem die Bauteilnutzungsdauer begrenzenden Bauteilverschleiß führen, und mit einer Einrichtung zur Bestimmung der Bauteilnutzungsdauer und einer verschleißbedingten Bauteil-Restnutzungsdauer. Erfindungsgemäß wird ein sich zeitversetzt wiederholender, jeweils gleicher Betriebszustand vorbestimmt, dem eine jeweils gleiche, periodisch wirkende Verformungskraft zugeordnet ist, durch die das elastisch verformbare Bauteilmaterial periodisch verformt wird, wobei durch Walkarbeit ein Energieeintrag mit einem messbaren Temperaturanstieg im Vergleich zu einer Umgebungstemperatur erfolgt und wobei der jeweilige Temperaturanstieg als Kenngröße im Verlauf einer Bauteilnutzungsdauer entsprechend einer abnehmenden Bauteilsteifigkeit größer wird. Ein solcher vorbestimmter Betriebszustand wird jeweils von einer Messund Auswerteeinheit erkannt und ein Messvorgang durch ein Startsignal selbsttätig gestartet, wobei mit wenigstens einem bauteilzugeordneten Temperatursensor, der aktuelle Temperaturanstieg im Vergleich zur Umgebungstemperatur als Kenngröße für eine aktuelle Bauteilsteifigkeit gemessen und jeweils in einer Messkurve gespeichert und verglichen wird.

EFFECT OF SHREDDING PARAMETERS ON THE FORMATION OF AIRBORNE FIBER DUST DURING MECHANICAL RECYCLING OF FIBER-REINFORCED THERMOPLASTICS - Hopp, Matthias; Tölle, Lisa (Proceedings of the 20th European Conference on Composite Materials)

Qualification of Different Carbon Fiber Reinforced Polyether Ether Ketone Materials for the FFF Process - Moritzer, Elmar; Wächter, Julian

Bewertung von IR-Schweißverbindungen an kurzfaserverstärkten Thermoplasten mittels digitaler Bildkorrelation - Gevers, Karina; Schraa, L; Uhlig, K; Töws, P; Stommel, M

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Schöppner, Volker; Vogtschmidt, Sascha

On the Wave to Successful Mixing - Schöppner, Volker; Dörner, M.; Frank, Maximilian; Schall, Christoph

Batch Constrained Bayesian Optimization for UltrasonicWire Bonding Feed-forward Control Design - Hesse, Michael; Hunstig, Matthias; Timmermann, Julia; Trächtler, Ansgar (Proceedings of the 11th International Conference on Pattern Recognition Applications and Methods (ICPRAM))
Ultrasonic wire bonding is a solid-state joining process used to form electrical interconnections in micro and power electronics and batteries. A high frequency oscillation causes a metallurgical bond deformation in the contact area. Due to the numerous physical influencing factors, it is very difficult to accurately capture this process in a model. Therefore, our goal is to determine a suitable feed-forward control strategy for the bonding process even without detailed model knowledge. We propose the use of batch constrained Bayesian optimization for the control design. Hence, Bayesian optimization is precisely adapted to the application of bonding: the constraint is used to check one quality feature of the process and the use of batches leads to more efficient experiments. Our approach is suitable to determine a feed-forward control for the bonding process that provides very high quality bonds without using a physical model. We also show that the quality of the Bayesian optimization based control outperforms random search as well as manual search by a user. Using a simple prior knowledge model derived from data further improves the quality of the connection. The Bayesian optimization approach offers the possibility to perform a sensitivity analysis of the control parameters, which allows to evaluate the influence of each control parameter on the bond quality. In summary, Bayesian optimization applied to the bonding process provides an excellent opportunity to develop a feedforward control without full modeling of the underlying physical processes.
Keywords: Bayesian optimization; Wire bonding; Feed-forward control; model-free design

Influence of Processing Glass-Fiber Filled Plastics on Different Twin-Screw Extruders and Varying Screw Designs on Fiber Length and Particle Distribution - Rüppel, Annette; Wolff, Susanne; Oldemeier, Jan Philipp; Schöppner, Volker; Heim, Hans-Peter (Polymers)
Due to their valuable properties (low weight, and good thermal and mechanical properties), glass fiber reinforced thermoplastics are becoming increasingly important. Fiber-reinforced thermoplastics are mainly manufactured by injection molding and extrusion, whereby the extrusion compounding process is primarily used to produce fiber-filled granulates. Reproducible production of high-quality components requires a granulate in which the fiber length is even and high. However, the extrusion process leads to the fact that fiber breakages can occur during processing. To enable a significant quality enhancement, experimentally validated modeling is required. In this study, short glass fiber reinforced thermoplastics (polypropylene) were produced on two different twin-screw extruders. Therefore, the machine-specific process behavior is of major interest regarding its influence. First, the fiber length change after processing was determined by experimental investigations and then simulated with the SIGMA simulation software. By comparing the simulation and experimental tests, important insights could be gained and the effects on fiber lengths could be determined in advance. The resulting fiber lengths and distributions were different, not only for different screw configurations (SC), but also for the same screw configurations on different twin-screw extruders. This may have been due to manufacturer-specific tolerances.
Keywords: Polymers and Plastics; General Chemistry

Produktkennzeichnung durch lokal definierte Einstellung von ferromagnetischen Eigenschaften beim Drückwalzen von metastabilen Stahlwerkstoffen - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian (36. Aachener Stahlkolloquium – Umformtechnik “Ideen Form geben“)

A flow forming process model to predict workpiece properties in AISI 304L - Arian, Bahman; Oesterwinter, Annika; Homberg, Werner; Rozo Vasquez, Julian; Walther, Frank; Kersting, Lukas; Trächtler, Ansgar (19th Int. Conference on Metal Forming 2022)

Autonomes Putten mittels datengetriebener und physikbasierter Methoden - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (Proceedings - 32. Workshop Computational Intelligence: Berlin, 1. - 2. Dezember 2022)

Learning Data-Driven PCHD Models for Control Engineering Applications* - Junker, Annika; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Strom statt Gas: Nachhaltige Herstellung von Karosseriebauteilen - Pfeifer, Florian; Jungeilges, André; Behm, Jonathan (Transforming Economies)

Gekoppelte Simulation des resistiven Schnellerwärmens für Fertigungsprozesse mit integrierter Wärmebehandlung am Beispiel der Titanlegierung Ti-6Al-4V - Merten, Mathias; Klöppel, Thomas; Haufe, André; Kaiser, Maximilian Alexander; Wesendahl, Jan-Niklas; Konrad, Stefan (Workshop Warmblechumformung)
Der Beitrag liefert einen Überblick über die Möglichkeiten der gekoppelten multiphysikalischen numerischen Simulation mit dem Finite Elemente-Löser LS-DYNA. Am Beispiel der resistiven Schnellerwärmung einer Titanlegierung im Forschungsprojekt TISTRAQ erfolgt die Beschreibung der Vorgehensweise, der Eingangs- und Ergebnisgrößen sowie der weiteren Anwendung der Simulation im Forschungsprojekt. Im Fokus steht dabei die Ermittlung der lokalen Temperaturverläufe, deren Kenntnis eine Grundvoraussetzung für die Berechnung prozessabhängiger Materialkennwerte darstellt.

Heat transfer coefficient investigation for hot die quenching process of Ti-6Al-4V alloy - Kaiser, Maximilian Alexander; Rockicki, Pawel; Höschen, Fabian; Wesendahl, Jan-Niklas; Konrad, Stefan; Meyer, Thomas; Marten, Thorsten; Tröster, Thomas
In the aerospace industry processing of high strength titanium alloys is both resource and time consuming. That why a lot of efforts is put on development of new and highly advanced manufacturing processes as hot die quenching. The process is based on combination of elevated temperature plastic forming with modification of the microstructure due to heat treatment, and thus increase in the properties of finally shaped geometry. One of the most crucial factors in the hot die quenching process is heat transfer coefficient. It is a main driver for adjustment of basic process parameters, as selection of tool material or the strain rate, but also plays an important role while elaborating temperature field in the numerical model. Thus, the main scope of the research within the current study is to examinate the heat transfer coefficient (HTC) for titanium and tooling material, which correspond to a real forming process. New and unique test stand have been designed and presented together with preliminary experimental results, which are a basis for further numerical simulation model of the hot die quenching process.
Keywords: Ti-6Al-4V; heat transfer coefficient